Vliv lécby beta-adrenergními blokátory na beta-adrenergní receptory v myokardu dĕtí s Fallotovou tetralogií - Hynie, S; Samánek, M; Caisedo, M; Roznová, L; Hucín, B; Vislocký, I (Casopis lekaru ceskych, 1993)
Seventeen children with tetralogy of Fallot undergoing cardiac surgery were investigated for alteration in myocardial beta-adrenergic receptors (BAR) in dependence on the previous chronic administration with the beta-adrenergic blocker metipranolol. Binding parameters, Bmax (maximal binding capacity) and Kd (dissociation constant), in right ventricular tissue were assessed in direct saturation binding studies using 125I-pindolol. It can be concluded that a) chronic administration of metipranolol to nine patients in usual doses did not change either Bmax or Kd of BAR in the samples of right ventricle, and b) twelve hours interval between last dose of metipranolol and removal of tissue samples is sufficiently long to enable normalization of possible changes in the sensitivity of BAR. This finding is supported by the pot-operative course and the response to dopamine which did not differ in patients treated and untreated with metipranolol in the preoperative period. Thus, our results suggest that there is no apprehension of chronic application of beta-blockers in patients with tetralogy of Fallot which would negatively influence the response to dopamine during the operation and in the postoperative period.
Keywords: předškolní dítě; myokard; beta-adrenergní receptory; Infant; Humans; Metipranolol; Myocardium; Receptors, Adrenergic, beta; Tetralogy of Fallot; lidé; Fallotova tetralogie; kojenec; Child, Preschool; metipranolol